Quest for COVID-19 cure: integrating traditional herbal medicines in the modern drug paradigm - Pandey, Prativa; Basnet, Angisha; Mali, Aatish (Applied Science and Technology Annals, 2020)
The world is facing one of the biggest public health tragedies of our time, both in terms of socio-economic loss and death tolls due to the coronavirus COVID-19 pandemic. In a frantic race to find treatment for COVID-19, many interventions to discover drugs and vaccines are being expedited. Similarly, traditional herbal medicines are also being explored to find a cure for COVID-19. There are many traditional medicines that have exhibited promising antiviral and immuno-modulating properties against a plethora of infectious diseases like influenza, malaria, tuberculosis, and even COVID-19. Traditional medicine is an integral part of culture and practices in many countries with a vast and rich history of treating diseases. However, scientific research-based drug development approaches and effective regulatory mechanisms, on par with modern medicine, should be implemented to ensure safety, efficacy and overall validity of traditional medicine. Incorporating evidence-based traditional medicines in modern drug development paradigms can help assure affordability, accessibility and acceptability of the treatment approach. Furthermore, it can create pharmacological synergism to tackle drug resistance. Altogether, every country should create a roadmap for modernization and revival of traditional knowledge to improve the health care system and be better prepared for health crises.